THE EFFECTIVENESS WAY FOR IMPROVING THE USING OF VOCABULARIES FOR GENERAL PUBLIC - Nelia Fariani Siregar; Otto Fajarianto; Titim Nurlia; Yhonanda Harsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is; (1) to determine whether it is effective to improve understanding of English vocabulary by reading English novels; (2) to find out the general public's preferences in choosing the language of the novel. The research uses a description method and an online questionnaire survey to find out the clear number of respondents' answers. Based on data collected through a Google form questionnaire distributed to social media. Based on the research that has been done, it can be concluded that: (1) reading English texts continuously causes respondents to get used to English vocabulary; (2) respondents prefer English novels to Indonesian ones.